2020
DOI: 10.3390/genes11020183
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Identifying the Different Molecular Genetic Markers Related to Production Performance and Meat Quality in Longissimus Dorsi Tissues of MG × STH and STH Sheep

Abstract: Crossbred sheep have many prominent traits, such as excellent production performance and high-quality meat, when compared to local sheep breeds. However, the genetic molecular markers related to these characteristics remain unclear. The crossbred MG × STH (small-tailed Han sheep (STH) × Mongolian sheep (MG)) breed and the STH breed were selected to measure production performance and meat quality. We used 14 indexes of production performance and meat quality, which in the MG × STH population showed significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
(66 reference statements)
0
15
1
Order By: Relevance
“…Recently the HEG1 gene was identified as one of several novel genes associated with human skeletal muscle growth, exhibiting a significant correlation with the percentage of change in lean mass [66,67]. In a comparative transcriptomic analysis aimed to identify differentially expressed genes related to product performance and meat quality from the longissimus dorsi in sheep, Cheng et al (2020) [68] identified six differentially expressed genes, including HEG1 [66].…”
Section: Discussionmentioning
confidence: 99%
“…Recently the HEG1 gene was identified as one of several novel genes associated with human skeletal muscle growth, exhibiting a significant correlation with the percentage of change in lean mass [66,67]. In a comparative transcriptomic analysis aimed to identify differentially expressed genes related to product performance and meat quality from the longissimus dorsi in sheep, Cheng et al (2020) [68] identified six differentially expressed genes, including HEG1 [66].…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore inferred that the number of samples has no adverse effect on our results. Finally, in previous studies about the transcriptome profiles of the skeletal muscle in sheep ( Arora et al, 2019 ; Cheng et al, 2020 ), cattle ( Cassar-Malek et al, 2017 ; Zhang et al, 2018 ) and goats ( Lin et al, 2017 ; Wang et al, 2017 ; Zhan et al, 2018 ), the number of samples per condition was less than four.…”
Section: Discussionmentioning
confidence: 97%
“…The wingless-type MMTV integration site family (Wnt), mitogen-activated protein kinase (MAPK) and phosphatidylinositol-3-kinase (PI3K)-Akt signaling pathways have been reported to play key roles in myogenesis, muscle growth, regeneration and differentiation in mice ( Tajbakhsh et al, 1998 ; Liu et al, 2017 ), chicken ( Elia et al, 2007 ; Abu-Elmagd et al, 2010 ), and human ( Otto et al, 2008 ; Kornasio et al, 2009 ). In recent years, RNA-Seq has been widely used to analyze genetic mechanisms underlying skeletal muscle growth and development in pigs ( Óvilo et al, 2014 ; Xu et al, 2018 ), cattle ( Silva-Vignato et al, 2017 ; Zhang et al, 2018 ), and sheep ( Sun et al, 2016 ; Cheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are also essential for satellite cell function and muscle development, according to muscle-specific ablation of Dicer, a critical enzyme for the generation of precursor (pre)miRNAs (11). RNA-SEQ has been widely employed in recent years to investigate the genetic mechanisms of skeletal muscle growth and development in various domestic animals (12,13). Muscle-specific miRNAs, such as miR-1, miR-133, and miR-206, have been found to play an essential role in the proliferation, differentiation, and regeneration of skeletal muscle cells in studies (14-16).…”
Section: Introductionmentioning
confidence: 99%